Mega-regional trade agreements: Implications for the African, Caribbean and Pacific countries - Peter Draper; Simon Lacey; Yash Ramkolowan (European Centre for International Political Economy (ECIPE), 2014)
In the wake of the ninth WTO ministerial conference in Bali, in December 2013, there is renewed optimism that the WTO can deliver something. The time is therefore right for member states to strategically reappraise their positions in the context of their overarching domestic and regional trade strategies. Central to any appraisal is the new geopolitical reality represented by the free trade agreements (FTAs) being negotiated by the major industrial powers. Led by the U.S., the Trans Pacific Partnership (TPP) and the Transatlantic Trade and Investment Partnership (TTIP) are wide in scope and deep in ambition. They are laden with many implications for non-party states and for the global trading system. Partly a product of the impasse in the WTO, these potential agreements have also sucked negotiating energy out of the WTO. These FTAs are also a product of the geopolitical rise of China, to the point where it is not far from asserting leadership of the global trading system. Therefore, the U.S. and its EU counterparts are also driven by their own geopolitical imperative of locking in access to key markets and regions, a thrust that has direct implications for ACP member states. Not surprisingly, China and other major developing economies are responding with initiatives of their own, such as the Regional Cooperation in Asia and the Pacific negotiations. Hence there is renewed impetus behind FTA negotiations across the world. (...)
Keywords: 330